Evaluation of relationship between meteorological parameters and air pollutant concentrations during winter season in Elazig, Turkey - Akpinar, S.; Öztop, Hakan Fehmi; Akpinar, Ebru Kavak (Springer, 2008)
In recent years, due to the rapid increase in population density, building density and energy consumption, the outdoor air quality has deteriorated in the crowded urban areas of Turkey. Elazig city, which is located in the east Anatolia region of Turkey, is also influenced by air pollutants. In the present study, relationship between monitored air pollutant concentrations such as SO2 and the total suspended particles (TSP) data and meteorological factors such as wind speed, temperature, relative humidity, solar radiation and atmospheric pressure was investigated in months of October, November, December, January, February, and March during the period of 3 years (2003, 2004 and 2005) for Elazig city. According to the results of linear and non-linear regression analysis, it was found that there is a moderate and weak level of relation between the air pollutant concentrations and the meteorological factors in Elazig city. The correlation between the previous day's SO2, TSP concentrations and actual concentrations of these pollutants on that day was investigated and the coefficient of determination R-2 was found to be 0.64 and 0.54, respectively. The statistical models of SO2 and TSP including all of meteorological parameters gave R-2 of 0.20 and 0.12, respectively. Further, in order to develop this model, previous day's SO2 and TSP concentrations were added to the equations. The new model for SO2 and TSP was improved considerably with R-2=0.74 and 0.61, respectively.
Keywords: Sulphur dioxide; Total suspended particles (TSP); Meteorological parameters; Regression analysis; Elazag-Turkey